The Interaction Between Understanding of Critical Thinking and Teaching/Learning of Critical Thinking Skills - Indrašienė, Valdonė; Jegelevičienė, Violeta; Merfeldaitė, Odeta; Penkauskienė, Daiva; Pivorienė, Jolanta; Railienė, Asta; Sadauskas, Justinas; Valavičienė, Natalija (Pedagogika, 2023)
This article aims to present the interaction between understanding of critical thinking and teaching and learning of critical thinking skills in higher education in Lithuania. Representative quantitative research was implemented, and 152 teachers and 1512 students took part in the survey. Exploratory factor analysis revealed two factors – the rigidity and elasticity of the conception of critical thinking – that have an impact on teaching and learning of critical thinking skills.